Age peculiarities in the change of aldoketoreductase spectrum in rat blood - V. V. Davydov; I. V. Matveeva; L. L. Sukhova (Acta Biomedica Scientifica, 2016)
In order to reveal the causes of age-related changes in sensitivity of the organism to oxidative stress, the spectrum of aldoketoreductases in blood serum of rats of different ages was investigated. It was discovered that 0.5- and 24-month old rats have the similar spectrum of aldoketoreductase in the blood. There are only four electrophoretic fractions of aldoketoreductases in their spectrum. The share of 3rd fraction increases the spectrum of 1.5-, 2- and 3- month old rats. The pubertal rats contain additional 5th fraction in aldoketoreductase spectrum of the blood. This electrophoretic fraction has maximal electrophoretic mobility, but there is inconstancy in spectrum. There are 6 electrophoretic fractions of aldoketoreductases in the blood of 3-month old rats. Two of them with maximal electrophoretic mobility are absent in the spectrum of 0.5- and 24- month old rats. There are the same shares of 3rd and 4th fraction in the aldoketoreductase spectrum of the blood 12-month old rats, and 5th fraction there is inconstancy. The cause of age-related changes in the aldoketoreductase spectrum of blood may be coupled with existence of age-related differences in the gene expression of the encoded enzymes of aldoketoreductase family. Due to the fact that 0.5- (early childhood) and 24-month old (senescence) rats have similar aldoketoreductase spectrum of the blood, we propose that the cause ofthat phenomenon coupled with age-related changes in the production and secretion of sex steroids.